Our American Israel : the story of an entangled alliance - Kaplan, Amy (Harvard University Press, 2018)
How did a Jewish state come to resonate profoundly with Americans in the twentieth century? Since WWII, Israel's identity has been entangled with America's belief in its own exceptionalism. Turning a critical eye on the two nations' turbulent history together, Amy Kaplan unearths the roots of controversies that may well divide them in the future.--